Exploring error patterns in English writing: a pathway to innovative multimodal instructional material - Tupas, Joshua B.; Bacio, Jr., Salvador P. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Considered as a crucial element that leads to better academic performance, Filipino learners always aim to master English language skills. Among various factors that affect the learning of English language skills, the availability of resources that cater to a diverse set of learners is important. Using semiotic or multimodal resources may help teachers assist students in enhancing their macro skills in the English language. This developmental research aimed to design, develop and evaluate a multimodal instructional material (IM) based on students identified common errors in writing. English major education students were selected as participants as they are important role-players in enhancing the future generation of learners in the English language. There were 39 freshman bachelor of secondary education (BSEd) English major students, three English teachers, two curriculum experts, and one information technology expert participated in the study. A panel of experts validated the instruments, which included the questionnaire to gauge the respondents’ writing skills, the adapted rubric for writing proficiency, and the adapted evaluation form for printed IM exclusively used by the university. Results of the study revealed that the respondents’ writing skills were poor. The evaluation conclusively showed that the IM was very acceptable for classroom use and teaching. It was recommended that the developed multimodal IM be used as a supplementary workbook to facilitate the need for primary English textbooks for the freshman BSEd English major students.